2014
DOI: 10.1590/s1677-5538.ibju.2014.06.07
|View full text |Cite
|
Sign up to set email alerts
|

Urine leak in minimally invasive partial nephrectomy: analysis of risk factors and role of intraoperative ureteral catheterization

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Purpose: To investigate risk factors for urine leak in patients undergoing minimally invasive partial nephrectomy (MIPN) and to determine the role of intraoperative ureteral catheterization in preventing this postoperative complication. Materials and Methods: MIPN procedures done from September 1999 to July 2012 at our Center were reviewed from our IRB-approved database. Patient and tumor characteristics, operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
11
0
5
Order By: Relevance
“…In all, 21 OPN and 17 LPN articles were reviewed (Table ). The reported urinary leak rates ranged from 1.0% to 17.4% for OPN and 1.6–16.5% for LPN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 21 OPN and 17 LPN articles were reviewed (Table ). The reported urinary leak rates ranged from 1.0% to 17.4% for OPN and 1.6–16.5% for LPN.…”
Section: Resultsmentioning
confidence: 99%
“… reported an OPN urinary leak rate of 1.1%, while Zargar et al. reported an overall urinary leak rate of minimally invasive PN (LPN and RPN) of 3% (31/1 019). Zargar and the group from Cleveland Clinic also note that a surgeon's early operative experience predicts urine leak; therefore it is reasonable to surmise that the evolving urinary leak rate is lower than reported.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of urinary fistula after partial nephrectomy has ranged from 1% to 17.4% [26]. However, more recent studies report urinary leakage rates between 0.6% and 3% [27,28]. Risk factors include hilar tumor location, tumor size, blood loss, and need for pelvicalyceal repair [26,2931].…”
Section: Discussionmentioning
confidence: 99%
“…None of our patients had intraoperative problems or postoperative urine extravasations associated with refraining from catheterization. Zargar et al [22] reported that routine ureteral catheterization is not necessary in minimally invasive PN (LPN and RAPN) but it is necessary in cases where the mass is close to the collecting system or when novice surgeons are performing the procedure. They reported that routine ureteral catheterization did not provide any benefits in blocking urine extravasation.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that routine ureteral catheterization did not provide any benefits in blocking urine extravasation. [22] Tomaszewski et al [23] also concluded that renal pelvic anatomy which is measured by renal pelvic score can also predict urine extravasation after open and robotic partial nephrectomy. Based on the renal pelvic scoring system, preoperative identification of the patients with increased risk for urine leak should be considered in perioperative management.…”
Section: Discussionmentioning
confidence: 99%